Legal education in the university: the ways to improvement - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with problem of realization of measures by the higher education institution, which areaimed at creating conditions for students to acquire the amount of legal knowledge and skills in their application, are required for exercising their rights and freedoms, as well as exercising of their duties.